2017
DOI: 10.1016/j.schres.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neuropsychological features of violence in schizophrenia: A prospective cohort study

Abstract: The increased risk of violence in schizophrenia has been linked to several environmental, clinical and neuropsychological factors, including executive dysfunction.However, data about the nature of these effects are mixed and controversial. The main aim of this study was to investigate the relationship between clinical and neuropsychological factors with violence risk in patients with schizophrenia, taking into account current psychopathology and lifetime alcohol use. We compared a sample of patients living inR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Multiple GLM analysis also showed that PCSU were more likely to show violent behavior. Consistent with previous results (Bulgari et al, 2017), personality disorders and low negative BPRS-E symptoms must be considered, especially for residential patients with current use. Our findings suggest that specific interventions to reduce aggressive and violent behavior should be targeted toward patients with this clinical profile.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple GLM analysis also showed that PCSU were more likely to show violent behavior. Consistent with previous results (Bulgari et al, 2017), personality disorders and low negative BPRS-E symptoms must be considered, especially for residential patients with current use. Our findings suggest that specific interventions to reduce aggressive and violent behavior should be targeted toward patients with this clinical profile.…”
Section: Discussionsupporting
confidence: 87%
“…Italian clinical studies showed a direct correlation between symptoms of acute psychosis and the occurrence of aggressive behaviors, with the presence of disorientation, motor hyperactivity, hostility-suspiciousness, grandiosity and borderline and passive-aggressive personality traits predicting a change for the worse in aggressive behavior, from verbal to physical [ Another recent Italian cohort study [73] investigated the relationship between clinical and neuropsychological factors with risk of aggression in inpatients with schizophrenia. Physically aggressive patients showed a higher number of compulsory admissions, higher anger, and less negative symptoms as compared to non-aggressive patients.…”
Section: Psychiatric Diagnosismentioning
confidence: 99%
“…A recent cohort Italian study [73] compared a sample of patients with schizophrenia and a history of physical aggression to patients with schizophrenia matched by age, gender, and alcohol abuse but without such a history. During a 1-year follow-up, patients with a history of aggression resulted more likely to be violent.…”
Section: History Of Aggressionsmentioning
confidence: 99%
“…Another strong predictor of aggressive behavior is a history of violence. This result is confirmed by the VIORMED project (Bulgari et al [12]; Candini et al [14]; de Girolamo et al [21]) and by several studies on patients with SMD and/or offenders (Fazel et al [25,26]; Lund et al [38]). At the same time, the present study points out that people with a history of violence are characterized more frequently by poor metacognitive functioning compared to patients without such history; this data is supported by other studies [1,2,30].…”
Section: Predictors Of Aggressive and Violent Behavior And The Role Omentioning
confidence: 58%